A New Approach to Elementary Learning: An Interactive Digital Module for Critical Thinking with Articulate Storyline - Yuli Mulyawati; Elly Sukmanasa; R. Teti Rostikawati; Nurafifah Deas Maharani; Aisyah Nur Azizah (FKIP UNIVERSITAS PAKUAN, 2024)
This research aims to develop an interactive digital module based on Articulate Storyline to improve the critical thinking skills of elementary school students. A research and development (R&D) approach with the ADDIE model is used in the development of this module, which includes the stages of needs analysis, interactive module design, development, implementation and evaluation. The research was conducted in fifth grader at one of state elementary school, Bogor City. The results of the expert validation show the feasibility of the material (90%), media (87%) and language (85%), which fall into the category of